Legal and Ethical Arrangements for Medical Record Filling by Doctors: A Normative Study - Mubarak, Muas; Darmawan, Didit; Saputra, Rio (Bulletin of Science, Technology and Society, 2023)
Medical law in Indonesia began to develop since 1981, triggered by the case of doctor Seitianingrum in Pati, which highlighted the importance of legal responsibility in medical practice. Medical records have a crucial role, both as administrative documents and legal evidence, in accordance with the Minister of Health Regulation Number 24 Year 2022. Medical records include important data related to patient identity, diagnosis, medical treatment, and other health services. However, mistakes in filling out medical records still often occur due to negligence. Although classified as minor negligence (culpa levis), these mistakes can have legal implications, both in the form of administrative, civil, and criminal sanctions. This study uses a normative approach to analyze laws and regulations, legal principles, and ethical standards that regulate the obligations of doctors in managing medical records. The results show that compliance with legal and ethical obligations is very important to protect patient rights, improve the quality of health services, and maintain the professionalism of doctors. Mistakes in completing medical records not only have an impact on legal aspects, but also violate the principles of medical ethics. Recommendations from this study include improving the competence of medical personnel through continuous training, implementing information technology in medical record management, and educating patients about their rights. These efforts are expected to strengthen legal and ethical compliance in medical practice, create better quality health services, and protect all involved sides.